Selection of Sediment Retention Structure Type in Coastal Reservoir (Case Study of Terboyo Retention Pond, Semarang) - Susanto, Deddy; Wahyudi, Slamet Imam; Soedarsono, Soedarsono (Universitas Ibn Khaldun Bogor, 2025)
To overcome the problem of flooding and tidal flooding in the city of Semarang, especially in the eastern part of Semarang, the Semarang-Demak Toll Road was built which is integrated with the sea wall. The sea wall is planned to prevent sea water from entering the land area, however, the sea wall will also block the direct flow of several rivers to the sea so that a fairly large coastal reservoir is needed. As in general, coastal reservoirs and retention ponds often experience sedimentation problems which have an impact on the economic value of the reservoir concerned, while in the planning of coastal reservoirs and retention ponds in general they are not equipped with sediment retaining structures. From this study, the results of the selection of the right type of sediment retaining structure to be applied in coastal reservoirs were obtained. The selection of the type of sediment retaining structure in this study used the AHP (Analytical Hierarchy Process) method, which is a decision support model that involves experts who have knowledge and experience in planning or implementing retention ponds or sedimentation in river estuaries. From the results of the global priority analysis above, the weight of each alternative sediment retaining structure is obtained, namely a fixed dam of 33.21%, a vertical movable dam with an upper opening of 31.35%, without a sediment retaining structure of 19.61%, a vertical movable dam with a lower opening of 15.84%. From the results of the AHP analysis above, the highest weight was obtained, which was then used as a decision maker to choose the type of building with the highest value, namely a sediment retaining structure in the form of a permanent dam.